CTA Project Completion Report: Promoting inclusive, sustainable and responsible fisheries value chains in Seychelles and the IOC region - Fautrel, Vincent; Ba, Aichetou (Technical Centre for Agricultural and Rural Cooperation, 2020)
Aiming at improving the governance of the fisheries sector and strengthening the development of more inclusive and sustainable fisheries value chains in the Seychelles and the IOC region, the activities of the project were implemented in partnership with the following partners: • Seychelles Fisheries Authority (SFA) • Seychelles Fishers and Boat Owners Association (FBOA) • Fédération des Pêcheurs Artisans de l’Océan Indien (FPAOI) • ABALOBI (ICT start-up based in Cape Town, South Africa)